Effect of fly ash on the Li2O-B2O3 system: structural study by pulse echo technique - Saddeek, Y. B.; Azooz, M. A.; Kenawy, S. H. (Archives of Acoustics, 2005)
Fly ash obtained from Toshkey project, which in turn was delivered from France, is a valuable source of many oxides such as SiO2, Al2O3, Fe2O3, CaO and MgO. These oxides can provide a useful preliminary source for the preparation of glasses. Glass of the system 10 Li2O-90 B2O3 (wt %) has been prepared. The progressive addition of fly ash to this type of glass was made to study its effect on the chemical and physical properties of the parent glass. Room temperature ultrasonic measurements were performed by pulse-echo method. The densities of the prepared samples were measured to justify the packing arrangements of the constituent oxide. The variations in densities and ultrasonic velocities of the prepared samples containing progressive fly ash contents were correlated and discussed. The values of elastic moduli (including Young's modulus, bulk modulus, shear modulus and Poisson's ratio) were compared with those theoretically calculated in terms of Makishima-Mackenzie model and a model proposed by Rocherulle et al.